Dalton Trumbo’s Johnny Got His Gun and the Centenary of the End of the Great War (American & British Studies Annual, 2019)
In November 2018, the centenary of the end of “the war to end all wars” was commemorated all around the world. World War I affected millions of people and had a profound impact on literature and culture. The paper discusses Dalton Trumbo’s 1939 pacifist novel Johnny Got His Gun and its late 20th century legacy. Although the novel was published long after the war’s end, it remains one of the most powerful anti-war statements. Contrary to more famous World War I novels it does not deal with the disillusionment of the post-war generation. The story of a quadruple amputee which takes place entirely in the main protagonist’s head is a claustrophobic and nightmarish journey into the mind of a young boy trapped in himself, imprisoned in darkness. The novel frequently fell out of favor during the 20th century but it enjoyed its share of popularity in Czechoslovakia, thanks to Trumbo’s communist sympathies.
Keywords: World War I; Dalton Trumbo; Johnny Got His Gun; anti-war novel; pacifism; nightmare